Solid-State Self-Assembly of a Linear Hexanuclear Copper(II) Oxamate Complex with Alternating Antiferro- and Ferromagnetic Coupling - Ana Luísa A. Lage; Luísa A. Ribeiro; Antônio C. Doriguetto; Carlos B. Pinheiro; Wallace C. Nunes; Emerson F. Pedroso; Cynthia L. M. Pereira (Magnetochemistry, 2022)
In this work, we describe the synthesis, crystal structure and magnetic properties of the neutral hexacopper(II) complex of formula {[Cubpca)]2[Cu(dmopba)(H2O)]}2·4H2O (1), where Hbpca = bis(2-pyridylcarbonyl)-amide and dmopba = 4,5-dimethyl-1,2-phenylenebis(oxamato). Single crystals of 1 were obtained from the stoichiometric reaction (1:2 molar ratio) of the mononuclear copper(II) complexes (n-Bu4N)2[Cu(dmpba)] and [Cu(bpca)(H2O)2]NO3·2H2O through slow diffusion techniques in water as a solvent. The crystal structure of 1 shows that two neutral {[Cu(bpca)]2[Cu(dmopba)(H2O)]} trinuclear units are connected through double out-of-plane copper to outer carboxylate oxygen atoms resulting in a unique oxamate-bridged linear hexanuclear complex. Hydrogen bonds among adjacent entities involving the non-coordinated water molecules result in a supramolecular 3D network. Magnetic measurements on 1 show the occurrence of moderate antiferromagnetic intratrinuclear interactions between the copper(II) ions from the [Cu(bpca)]+ and [Cu(dmopba)(H2O)]2− fragments across the oxamate bridge and a weak intertrinuclear ferromagnetic interaction between the copper(II) ions that occurs between the two central [Cu(bpca)]+ fragments mediated by the carboxylate groups from the oxamate bridge [J = −31.96(2) cm−1 and J′ = +1.34(2) cm−1; H = J (S1·S2 + S2·S3 + S1′·S2′ + S2′·S3′) + J′ (S1·S1′)].